Dynamic 3D Locus Organization and Its Drivers Underpin Immunoglobulin Recombination - Rogers, Carolyn H.; Mielczarek, Olga; Corcoran, Anne E. (Frontiers in Immunology, 2021)
A functional adaptive immune system must generate enormously diverse antigen receptor (AgR) repertoires from a limited number of AgR genes, using a common mechanism, V(D)J recombination. The AgR loci are among the largest in the genome, and individual genes must overcome huge spatial and temporal challenges to co-localize with optimum variability. Our understanding of the complex mechanisms involved has increased enormously, due in part to new technologies for high resolution mapping of AgR structure and dynamic movement, underpinning mechanisms, and resulting repertoires. This review will examine these advances using the paradigm of the mouse immunoglobulin heavy chain (Igh) locus. We will discuss the key regulatory elements implicated in Igh locus structure. Recent next generation repertoire sequencing methods have shown that local chromatin state at V genes contribute to recombination efficiency. Next on the multidimensional scale, we will describe imaging studies that provided the first picture of the large-scale dynamic looping and contraction the Igh locus undergoes during recombination. We will discuss chromosome conformation capture (3C)-based technologies that have provided higher resolution pictures of Igh locus structure, including the different models that have evolved. We will consider the key transcription factors (PAX5, YY1, E2A, Ikaros), and architectural factors, CTCF and cohesin, that regulate these processes. Lastly, we will discuss a plethora of recent exciting mechanistic findings. These include Rag recombinase scanning for convergent RSS sequences within DNA loops; identification of Igh loop extrusion, and its putative role in Rag scanning; the roles of CTCF, cohesin and cohesin loading factor, WAPL therein; a new phase separation model for Igh locus compartmentalization. We will draw these together and conclude with some horizon-scanning and unresolved questions.